Cloning and in silico study of an endoglucanase from a thermophilic bacterium isolated from a hydrothermal vent of West Kawio, Sangihe‐Talaud waters, North Sulawesi, Indonesia - Edvan Arifsaputra Suherman; Maelita Ramdani Moeis; Elvi Restiawaty (Universitas Gadjah Mada, 2019)
Endoglucanase is used in industries that apply high temperatures, such as bioethanol, detergent, paper, and animal feed industries. Most available endoglucanases have very low stability at high temperatures. Therefore, this study aimed to identfy a new thermostable endoglucanase that is able to maintain its actvity at high temperatures. Five isolates of thermophilic bacteria were previously isolated from the hydrothermal vent of West Kawio, Indonesia. Among them, the DSI2 isolate showed the highest endoglucanase actvity, and was identfed and named as Bacillus safensis DSI2. The EgDSI2 gene was cloned from B. safensis DSI2. EgDSI2 is 1851 bp long encoding a protein of 616 amino acids. The encoded protein, EgDSI2, has high sequence identty to other B. safensis endoglucanases and was predicted with the Compute pI/Mw tool to be 69.41 kDa. EgDSI2 was high in hydrophobic amino acids. The enzyme had higher percentage of Ala andPro, and lower percentage of Gly compared to thermolabile endoglucanases from two Bacillus species. EgDSI2 harbored a catalytc domain belonging to glycosyl hydrolase family 9 (GH9) and a type 3 cellulose‐binding domain (CBM3). Propertes of endoglucanases with GH9‐CBM3 modular organizaton include actvity over a wide pH range, high optmum temperature, and thermostablity. Therefore, EgDSI2 has potental applicatons in the industries.